Financial Inclusion and Household Wellbeing in Sub Saharan Africa (Vallis Aurea, 2024)
This study provides evidence of the power of financial inclusion (access, quality and usage) on household wellbeing using data from teachers in primary schools of central and western Uganda. By means of a questionnaire approach to collect data, the study adopted a cross-sectional research approach. 326 respondents were responsive from a sample of 377 which yielded 86.5% response rate. Quantitative data were analyzed using Statistical Program for Social Sciences (SPSS) and Analysis of Moment Structures (AMOS). Drawing on the survey results, the paper clearly demonstrates that financial inclusion underpinned by minority influence theoretical lenses informs household wellbeing significantly in Uganda.